2019
DOI: 10.1111/tpj.14542
|View full text |Cite
|
Sign up to set email alerts
|

AtPER1 enhances primary seed dormancy and reduces seed germination by suppressing the ABA catabolism and GA biosynthesis in Arabidopsis seeds

Abstract: Summary Seed is vital to the conservation of germplasm and plant biodiversity. Seed dormancy is an adaptive trait in numerous seed‐plant species, enabling plants to survive under stressful conditions. Seed dormancy is mainly controlled by abscisic acid (ABA) and gibberellin (GA) and can be classified as primary and secondary seed dormancy. The primary seed dormancy is induced by maternal ABA. Here we found that AtPER1, a seed‐specific peroxiredoxin, is involved in enhancing primary seed dormancy. Two loss‐of‐f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 69 publications
0
54
0
Order By: Relevance
“…During cold stratification, expression of CYP707As that participate in ABA catabolism, and AtGA3ox1 that is involved in GA synthesis is elevated, leading to a high GA/ABA ratio, which promotes seed germination (Okamoto et al 2006; Su et al 2016; Chen et al 2019). The same expression control pattern was found with the atper1 mutant that has a dysfunctional seed‐specific peroxiredoxin (Chen et al 2019). In imbibed seeds, DELLA protein is degraded by the elevated GA to attenuate transcriptional activities of the DELLA‐ABI3‐ABI5 module, which accelerates germination.…”
Section: Abscisic Acid In Seed Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…During cold stratification, expression of CYP707As that participate in ABA catabolism, and AtGA3ox1 that is involved in GA synthesis is elevated, leading to a high GA/ABA ratio, which promotes seed germination (Okamoto et al 2006; Su et al 2016; Chen et al 2019). The same expression control pattern was found with the atper1 mutant that has a dysfunctional seed‐specific peroxiredoxin (Chen et al 2019). In imbibed seeds, DELLA protein is degraded by the elevated GA to attenuate transcriptional activities of the DELLA‐ABI3‐ABI5 module, which accelerates germination.…”
Section: Abscisic Acid In Seed Developmentmentioning
confidence: 99%
“…When exposed to high temperature, increased transcriptional activity of the DELLA‐ABI3‐ABI5 complex inhibits germination (Lim et al 2013). This balance between ABA and GA controls also involves interactions with other hormones like ethylene (ET), BR, strigolactone (SL) and auxin, as well as with ROS and NO, and with the temperature and light environmental cues (Chen et al 2009, 2019; Xiang et al 2014; Dekkers and Bentsink 2015; Shu et al 2016).…”
Section: Abscisic Acid In Seed Developmentmentioning
confidence: 99%
“…It is generally considered to be an inhibitor of bud dormancy (Bris et al, 1999; Wen et al, 2016). ABA and GA antagonistically control seed dormancy (Yamaguchi et al, 2007; Chen et al, 2019). Zhang et al (2018) used transcriptome to elucidate the relationship between hormone and sugar changes in different stages of dormancy and believed that GA and ABA were crucial in dormancy.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are the short non-coding RNAs (21–24 nucleotides) (Axtell and Meyers, 2018) that regulate the expression of target genes through complementary sequence matching. In plants, miRNAs regulate the expression of various genes in cluding transcription factors (Jung et al, 2014; Hernandez et al, 2017), stress-responsive proteins (Jagadeeswaran, G et al 2009; Sun, X. et al 2015), and other proteins, which are involved in the processes of growth and development (Jonesrhoades et al, 2006; Curaba et al, 2013; Chen et al, 2019), disease resistance (Feng et al, 2012; Yu et al, 2017; Jiang et al, 2018), abiotic stress response (Zhan et al, 2012; Zheng et al, 2015; Singh et al, 2017) and physiology (Gao et al, 2012a; Ma et al, 2019). Although the regulation of genes by miRNA is indirect, it is believed that miRNAs play essential roles in plant development.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, seed aging takes place, and an intensive degradation of nucleic acids and proteins occurs. Interestingly, it was recently demonstrated that AtPER1, a seed-specific peroxiredoxin, eliminates ROS to suppress ABA catabolism and GA biosynthesis, and thus improves the PD and make the seeds less sensitive to adverse environmental conditions [ 21 ]. In this Special Issue, Katsuya-Gaviria et al [ 22 ] review in detail the biological significance of nucleic acid oxidation caused by ROS during PD and germination.…”
Section: Ros and Nucleic Acid Modifications During Seed Dormancymentioning
confidence: 99%